Music and poetry in the middle ages: a guide to research on French and Occitan song, 1100-1400 - Switten, Margaret L. (New York & London Garland Publishing, 1995)
This important and timely bibliography brings modern critical and theoretical work to bear on medieval music and literature, primarily poetry. Entries include material on performance practice and styles, reflecting the enormous growth of interest in early music soloists and ensembles and medieval instruments. Switten covers the period from the eleventh century to approximately 1500 and cites entries in French, Italian, German, and English, thus encompassing the entire field of medieval music and literature for students and scholars.